2024
DOI: 10.1371/journal.pone.0298211
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking cyclophilin B, but not cyclophilin A, are protected from the development of NASH in a diet and chemical-induced model

Winston T. Stauffer,
Asha Z. Goodman,
Michael Bobardt
et al.

Abstract: Cyclophilins are a diverse family of peptidyl-prolyl isomerases (PPIases) of importance in a variety of essential cellular functions. We previously reported that the pan-cyclophilin inhibitor drug reconfilstat (CRV431) decreased disease in mice under the western-diet and carbon tetrachloride (CCl4) non-alcoholic steatohepatitis (NASH) model. CRV431 inhibits several cyclophilin isoforms, among which cyclophilin A (CypA) and B (CypB) are the most abundant. It is not known whether simultaneous inhibition of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The Gallay lab recently demonstrated that mice lacking CypB, unlike those lacking CypA, were protected from non-alcoholic steatohepatitis (NASH) in both dietary and chemically induced models. ( Stauffer et al, 2024 ). The resulting disruption of collagen folding and export, a central facilitation of liver fibrosis, is the predicted mechanism protecting mice from the development of NASH.…”
Section: Overview Of Ppiases and The Cyclophilin Familymentioning
confidence: 99%
“…The Gallay lab recently demonstrated that mice lacking CypB, unlike those lacking CypA, were protected from non-alcoholic steatohepatitis (NASH) in both dietary and chemically induced models. ( Stauffer et al, 2024 ). The resulting disruption of collagen folding and export, a central facilitation of liver fibrosis, is the predicted mechanism protecting mice from the development of NASH.…”
Section: Overview Of Ppiases and The Cyclophilin Familymentioning
confidence: 99%
“…Cyclophilin A (PPIA, CypA) is a cytosolic enzyme which can be secreted and has been shown to play important roles in inflammation [26,27] and the lifecycle of multiple viruses such as HIV, HCV, and HBV [27][28][29][30]. Cyclophilin B (PPIB, CypB) localizes to the endoplasmic reticulum where it serves as a chaperone, aiding in the folding of nascent proteins such as collagen [31][32][33][34]. Cyclophilin D (PPIF, CypD) is a component of the mitochondrial permeability transition pore (mPTP) where it can influence pore sensitivity and mitochondrial permeability [35][36][37].…”
Section: Introductionmentioning
confidence: 99%